Land Use Dinamics and Vegetation Density Based On Sentinel-2 Imagery In The Malili Sub Watershed, East Luwu District. - Safira, Nindya (Universitas Andi Djemma Palopo, 2025)
Land use changes in the Malili Sub-Watershed, East Luwu Regency, continue to increase due to the pressure of human activities, especially nickel mining, which has the potential to affect vegetation cover and hydrological function. Although studies of land use change have been widely conducted in various watersheds in Indonesia, long-term research integrating the analysis of land use change and vegetation dynamics at the sub-watershed scale is still limited. This study aims to analyze land use changes and vegetation density levels in the Malili Sub-Watershed in 2015 and 2024 using Sentinel-2 imagery through the Normalized Difference Vegetation Index (NDVI) approach and guided classification Maximum Likelihood Classification (MLC). The results showed a decrease in the area of primary dryland forest from 268.81 ha to 111.74 ha. On the other hand, secondary dryland forests increased by 128.07 ha and shrubs increased by 69.17 ha. The NDVI value in 2015 ranged from −0.18 to 0.65 and increased in 2024 to −0.09 to 0.67, indicating the predominance of medium to high density vegetation. The accuracy test resulted in an Overall Accuracy of 90%, so the classification map was considered feasible. The uniqueness of this research lies in the integration of NDVI and transition matrix in uncovering the dynamics of degradation and vegetation regeneration in mining areas.